Effect of Dietary Supplementation of Organic Acids on Performance, Nutrients Digestibility and Health of Broiler Chicks - Ghazalah, A.A.; Atta, A.M.; Elkloub, Kout; Moustafa, M.EL.; Shata , Riry F.H. (International Journal of Poultry Science, 2011)
This study was conducted to compare the effects of different types and levels of organic acids being Formic (0.25, 0.5 and 1.0% FA), Fumaric (0.5, 1.0 and 1.5% FUA), Acetic (0.25, 0.50 and 0.75% AC) and Citric Acids (1, 2 and 3% CA). A total number of 351 one d-old Arbor-Acres broiler chicks were randomly divided into 13 treatment groups, each in three replicates of 9 chicks per replicate. The first group was fed the basal diet without supplementation and served as control. While, the other groups were received the basal diet supplemented with the tested organic acids. The experiment was lasted when chicks were 42 d old. Performance, pH of some gastrointestinal tract (GI-tract) segments, organ morphology, cecal bacteria, blood metabolites and nutrients digestibility were measured. Results obtained could be summarized as follow: 1- Any of the tested organic acids increased significantly (p